QM calculations predict the energetics and infrared spectra of transient glutamine isomers in LOV photoreceptors - Andrikopoulos, Prokopis C; Chaudhari, Aditya S; Liu, Yingliang; Konold, Patrick E; Kennis, John T M; Schneider, Bohdan; Fuertes, Gustavo (Physical chemistry chemical physics, 2021)
Photosensory receptors containing the flavin-binding light-oxygen-voltage (LOV) domain are modular proteins that fulfil a variety of biological functions ranging from gene expression to phototropism. The LOV photocycle is initiated by blue-light and involves a cascade of intermediate species, including an electronically excited triplet state, that leads to covalent bond formation between the flavin mononucleotide (FMN) chromophore and a nearby cysteine residue. Subsequent conformational changes in the polypeptide chain arise due to the remodelling of the hydrogen bond network in the cofactor binding pocket, whereby a conserved glutamine residue plays a key role in coupling FMN photochemistry with LOV photobiology. Although the dark-to-light transition of LOV photosensors has been previously addressed by spectroscopy and computational approaches, the mechanistic basis of the underlying reactions is still not well understood. Here we present a detailed computational study of three distinct LOV domains: EL222 from Erythrobacter litoralis, AsLOV2 from the second LOV domain of Avena sativa phototropin 1, and RsLOV from Rhodobacter sphaeroides LOV protein. Extended protein-chromophore models containing all known crucial residues involved in the initial steps (femtosecond-to-microsecond) of the photocycle were employed. Energies and rotational barriers were calculated for possible rotamers and tautomers of the critical glutamine side chain, which allowed us to postulate the most energetically favoured glutamine orientation for each LOV domain along the assumed reaction path. In turn, for each evolving species, infrared difference spectra were constructed and compared to experimental EL222 and AsLOV2 transient infrared spectra, the former from original work presented here and the latter from the literature. The good agreement between theory and experiment permitted the assignment of the majority of observed bands, notably the ∼1635 cm-1 transient of the adduct state to the carbonyl of the glutamine side chain after rotation. Moreover, both the energetic and spectroscopic approaches converge in suggesting a facile glutamine flip at the adduct intermediate for EL222 and more so for AsLOV2, while for RsLOV the glutamine keeps its initial configuration. Additionally, the computed infrared shifts of the glutamine and interacting residues could guide experimental research addressing early events of signal transduction in LOV proteins.
Keywords: Models, Molecular; vztahy mezi strukturou a aktivitou; fotochemické procesy; Glutamine; Protein Binding; vodíková vazba; Structure-Activity Relationship; termodynamika; Spectrophotometry, Infrared; glutamin; Protein Conformation; isomerie; normální rozdělení; Phototropins; Flavin Mononucleotide; konformace proteinů; Hydrogen Bonding; molekulární modely; sekvence aminokyselin; spektrofotometrie infračervená; vazba proteinů; Photochemical Processes; fototropiny; flavinmononukleotid; Isomerism; Cysteine; Sphingomonadaceae; Amino Acid Sequence; Avena; Thermodynamics; Normal Distribution; oves; cystein